Masseter-to-Facial Cranial Nerve Anastomosis: A Report of 30 Cases. Issue 5 (15th June 2020) - Zotov, Alexander V; Rzaev, Jamil A; Chernov, Sergey V; Dmitriev, Alexander B; Kalinovsky, Anton V; Spallone, Aldo
Abstract: BACKGROUND: Facial nerve paralysis (FP) is a possible complication of cerebellopontine angle tumor surgery. Several donor nerves have been used in the past for facial reanimation. We report the results of 30 cases of masseter-to-facial anastomosis. OBJECTIVE: To prospectively evaluate the efficacy of V to VII anastomosis after FP. METHODS: In a prospective study, we included 30 consecutive patients with FP (20 women and 10 men) whose mean age was 48.8 yr (32-76 yr). In almost all cases, FP developed after cerebellopontine angle tumor surgery (29 patients), whereas in one case, FP occurred after skull base trauma. Pre- and postoperative evaluation of facial nerve function was performed using the House-Brackmann (HB) scale and the Sokolovsky scale, as well as by electromyography. Follow-up ranged from 11 to 51 mo and averaged 22 mo. RESULTS: All patients achieved functional recovery of the facial nerve from VI to either III or IV HB degree. Patients with short time FP showed significantly better postoperative recovery. CONCLUSION: The results of the V to VII anastomosis demonstrate a significant improvement of facial nerve function and virtually no complications.